PROSPECTS FOR IMPROVING THE DESIGN OF CLASSIC TRACTORS THROUGH THE INTEGRATION OF AUTOMATED MOTION CONTROL SYSTEMS - LYPNITSKY, ROMAN; CHMYKH, KATERYNA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article addresses the modernization of agricultural machinery through the integration of automated control systems, emphasizing this approach as one of the most effective means of enhancing the efficiency of agricultural production. It presents a comprehensive overview of current solutions in automatic control, outlining their specific characteristics and potential directions for further development. Particular emphasis is placed on their contribution to improving tractor performance, lowering operational costs, and creating safer and more comfortable working conditions for operators.A review of scientific literature highlights the principal benefits of adopting automated systems, including higher precision in technological processes, reduced fuel and lubricant consumption, more rational resource management, and decreased reliance on human factors. The study also examines the economic dimension of implementation, focusing on payback periods, possibilities for retrofitting existing machinery, and the adaptability of these technologies to the conditions of different agricultural enterprises.The influence of equipment-induced vibrations on the stability of RTK correction signals is analyzed, with findings showing that such vibrations may cause short-term disruptions in satellite reception and reduce positioning accuracy. To mitigate these issues, the article suggests solutions such as vibration-damping platforms, digital signal filtering, and advanced software-based correction techniques.In addition, the article considers the technical, financial, and organizational challenges that arise when retrofitting tractors with automated control systems. A comparative evaluation of different system types and their compatibility with existing machinery is provided, with key selection criteria for optimal modernization strategies clearly identified.Finally, practical guidelines are proposed for planning and executing tractor fleet upgrades, with attention to economic viability, technical integration, and future prospects for broader automation. The study’s outcomes may serve as a foundation for implementing innovations in agricultural production aimed at improving productivity and competitiveness.
Keywords: automated control; tractor; automation; RTK system